The application of electrochemical scanning probe microscopy to the interpretation of metalloprotein voltammetry - Davis, J; Hill, H; Bond, A (2000)
An accurate interpretation of metalloprotein voltammetry depends critically on a detailed understanding of the electrode surface and its interactions with surface-active proteins. Representations of the bioelectrochemical interface as a uniformly electroactive, flat electrode surface, where electron transfer takes place to non surface-interacting proteins, are unrealistic. The development of scanning probe technology allows both these surfaces and the interactions of biomolecules to be probed with an unprecedented resolution. In this review, the results of a number of scanning probe studies are presented, together with the theoretical implications for more realistic models required in the interpretation of metalloprotein voltammetric experiments. (C) 2000 Elsevier Science S.A.